Incidence of Reproductive Disorders in Cows in South Odisha: A One-Year Field Study - Sebastin Raju, F; Paidi, Saranya; Bhavya Charitha, B V S; Likitha, Nuka; Balagopalan, T P (The Indian Journal of Animal Reproduction, 2026)
A retrospective study was conducted on 1,136 cows (487 crossbred and 649 non-descript) presented at 71 Veterinary Ambulatory Clinics in Kasinagar and Gosani blocks of Gajapati district, Odisha, India from August 2023 to August 2024 to evaluate the incidence of reproductive disorders. Overall, 73.63% cases were anestrus and 26.37% repeat breeding. Crossbred Jersey cows showed higher postpartum anestrus (56.35%), while non-descript cows had more repeat breed ing (61.58%). Repeat breeding was most frequent in cows with BCS
Keywords: Anestrus; Repeat breeding; Crossbred Jersey cows